2016
DOI: 10.17795/jjnpp-27705
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Quercetin Hydrate With Those of Vitamin E on the Levels of IL-13, PDGF, TNF-α, and INF-γ in Bleomycin-Induced Pulmonary Fibrosis in Rats

Abstract: Background: Pulmonary fibrosis is a deadly and destructive disease. Various chemicals, drugs, and environmental factors are responsible for pulmonary fibrosis. The disease can also be idiopathic. A number of inflammatory mediators and cytokines, such

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Quercetin could also alleviate acute lung injury by decreasing oxidative stress and enhancing the activity of antioxidant enzymes [39]. When the inhibitory effects of quercetin were compared with those of vitamin E in the context of bleomycin-induced pulmonary fibrosis in rats, the antifibrotic activity of quercetin was higher than that of vitamin E [40], a well-known antioxidant. Additionally, Bidian et al evaluated the antioxidant effects of quercetin and curcumin on pleural inflammation induced by carrageenan and showed that in lung tissue, quercetin showed superior beneficial properties while in serum, curcumin had higher antioxidant effects compared to quercetin [41].…”
Section: Discussionmentioning
confidence: 98%
“…Quercetin could also alleviate acute lung injury by decreasing oxidative stress and enhancing the activity of antioxidant enzymes [39]. When the inhibitory effects of quercetin were compared with those of vitamin E in the context of bleomycin-induced pulmonary fibrosis in rats, the antifibrotic activity of quercetin was higher than that of vitamin E [40], a well-known antioxidant. Additionally, Bidian et al evaluated the antioxidant effects of quercetin and curcumin on pleural inflammation induced by carrageenan and showed that in lung tissue, quercetin showed superior beneficial properties while in serum, curcumin had higher antioxidant effects compared to quercetin [41].…”
Section: Discussionmentioning
confidence: 98%
“…Administration of quercetin hydrate (25, 50, and 75 mg/kg, i.p. ), in BLM‐induced pulmonary fibrosis in rats, reduced inflammatory fibrotic factors (platelet‐derived growth factor subunit B (PDGF‐β), IL‐13, and TNF‐α) but increased antifibrotic factors (INF‐γ) in the BALF (Malayeri et al, 2016). Quercetin also decreased total leukocyte count, MDA, TNF‐α, and MMP‐7 levels in the serum or the BALF, but increased SOD and CAT activities in BLM‐induced pulmonary fibrosis in rats (Verma et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The protective effect of quercetin in amiodarone-induced pulmonary toxicity in rats also reduced pulmonary histopathological changes, inflammatory lung cell infiltration, but increased CAT and GSH activities (Oka, Okon, & Osim, 2019). (Malayeri et al, 2016). Quercetin also decreased total leukocyte count, MDA, TNF-α, and MMP-7 levels in the serum or the BALF, but increased SOD and CAT activities in BLM-induced pulmonary fibrosis in rats (Verma et al, 2013).…”
mentioning
confidence: 90%
“…The results of laboratory and clinical studies showed that dexmedetomidine reduces inflammatory responses ( 21 , 22 ), and animal studies also showed inhibition of pro-inflammatory cytokines ( 23 ). In addition, the results of in vitro studies on whole human blood samples reported suppression of lipopolysaccharides, which produce pro-inflammatory mediators including TNF-α, interleukin-6, and IL-8 ( 24 , 25 ). Besides vasodilatory effects, alpha-2 agonists have sympathetic suppressive, sedative, and hypnotic effects ( 26 ).…”
Section: Introductionmentioning
confidence: 99%